Hypoxia decreases the T helper cell-suppressive capacity of synovial fibroblasts by downregulating IDO1-mediated tryptophan metabolism. (17th December 2019) - Kaul, Nathalie-Christin; Mohapatra, Soumya R; Adam, Isabell; Tucher, Christine; Tretter, Theresa; Opitz, Christiane A; Lorenz, Hanns-Martin; Tykocinski, Lars-Oliver
Abstract: Objective: The development of RA is linked to local infiltration of immune cells and to changes in the phenotype of synovial fibroblasts. Synovial fibroblasts possess the capacity to suppress T cell responses through indoleamine 2, 3-dioxygenase 1 (IDO1)-mediated tryptophan metabolism. However, synovial fibroblasts from RA patients are restricted in this immune-modulatory function. Moreover, hypoxic conditions are detected within synovial tissues of RA patients, with oxygen tensions of only 3.2% O2 . This study aims at investigating the effects of hypoxia on the interaction between T cells and synovial fibroblasts, particularly on the T cell-suppressive capacities of synovial fibroblasts. Methods: Synovial fibroblasts were cultured with Th cells under normoxic and hypoxic conditions (3% O2 ). Th cell proliferation was detected by flow cytometry. Tryptophan and kynurenine amounts were measured by HPLC. IDO1 expression and signal transducer and activator of transcription 1 (STAT1) phosphorylation were quantified by real-time PCR or western blot, and cytokine secretion by ELISA. Results: Hypoxic conditions strongly diminished the Th cell-suppressive capacities of both OA synovial fibroblasts and RA synovial fibroblasts. Accordingly, IDO1 mRNA and protein expression, STAT1 phosphorylation and tryptophan metabolism were greatly reduced in OA synovial fibroblasts by hypoxia. MMP-3, IL-6, IL-10 and IFNγ secretion were significantly decreased under hypoxia in synovial fibroblast-Th cell co-cultures, while IL-17A levels were elevated. Supplementation with IFNγ, a well-known inducer of IDO1 expression, could rescue neither IDO1 expression nor Th cell suppression under hypoxic conditions. Conclusion: Hypoxia strongly affected the crosstalk between synovial fibroblasts and Th cells. By reducing the efficiency of synovial fibroblasts to restrict Th cell proliferation and by increasing the expression of IL-17A, hypoxia might have implications on the pathophysiology of RA.